LAVENDER (LAVANDULA ANGUSTIFOLIA) AROMATHERAPY AS AN ALTERNATIVE TREATMENT IN REDUCING PAIN IN PRIMIPAROUS MOTHERS IN THE ACTIVE FIRST STAGE OF LABOR - Hilda Yani Karo Karo; Noor Pramono; Sri Wahyuni; Imam Djamaluddin Mashoedi; Leny Latifah (Belitung Nursing Journal, 2017)
Background: Labor and childbirth is an extremely painful process. Aromatherapy is considered as one of the nonpharmacological methods to reduce labor pain. Objective: To determine the effect of lavender (Lavandula Angustifolia) aromatherapy on the level of pain in primipara in the first stage of labor. Methods: A quasi-experimental research with pretest and posttest design with control group conducted between October until November 2016. Forty respondents selected using consecutive sampling, which 20 assigned in each group. a Numerical Rating Scale (NRS) pain scale was used. Paired and independent t-test were used for data analyses. Results: The results showed that the p-value of labor pain after intervention was 0.000 (<0.05), which indicated that there was statistically mean difference of labor pain between intervention group (6.10) and control group (4.05) in primipara in the first active stage of labor. Conclusion: The women in the lavender aromatherapy group reported lower intensity of labor pain. The intervention study could be practiced in the community health centers for pregnant women in order for them to apply this healing method.